Respuesta :

Answer:

7

Step-by-step explanation:

Simplify the following:

17 - 6×2 + 4/2

The gcd of 4 and 2 is 2, so 4/2 = (2×2)/(2×1) = 2/2×2 = 2:

17 - 6×2 + 2

-6×2 = -12:

17 + -12 + 2

17 + 2 = 19:

19 - 12

| 1 | 9

- | 1 | 2

| 0 | 7:

Answer:  7

Wolfyy

Hey!

-------------------------------

Solution:

Remember to follow PEMDAS.

= 17 - 6 • 2 + 4 / 2

= 17 - 12 + 2

= 5 + 2

= 7

-------------------------------

Answer:

7

-------------------------------

Hope This Helps :)

ACCESS MORE